2009
DOI: 10.1007/s11214-009-9553-2
|View full text |Cite
|
Sign up to set email alerts
|

Dynamo Scaling Laws and Applications to the Planets

Abstract: Scaling laws for planetary dynamos relate the characteristic magnetic field strength, characteristic flow velocity and other properties to primary quantities such as core size, rotation rate, electrical conductivity and heat flux. Many different scaling laws have been proposed, often relying on the assumption of a balance of Coriolis force and Lorentz force in the dynamo. Their theoretical foundation is reviewed. The advent of direct numerical simulations of planetary dynamos and the ability to perform them fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
257
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 281 publications
(288 citation statements)
references
References 57 publications
25
257
1
Order By: Relevance
“…Christensen & Aubert (2006) derived a magnetic field scaling relation for planets based on dynamo simulations that cover a broad parameter range. Recently, Christensen et al (2009) generalized the scaling law and showed that its predictions agree with observations for a wide class of rapidly rotating objects, from Earth and Jupiter to low-mass main sequence (spectral types K and M) and T Tauri stars (see also Christensen 2010). Here, we revisit the question of magnetic field strength at brown dwarfs and giant planets and the estimate for the radio flux from extrasolar planets, using this scaling law, which we believe to be on more solid grounds both theoretically and observationally than previously suggested scaling laws.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Christensen & Aubert (2006) derived a magnetic field scaling relation for planets based on dynamo simulations that cover a broad parameter range. Recently, Christensen et al (2009) generalized the scaling law and showed that its predictions agree with observations for a wide class of rapidly rotating objects, from Earth and Jupiter to low-mass main sequence (spectral types K and M) and T Tauri stars (see also Christensen 2010). Here, we revisit the question of magnetic field strength at brown dwarfs and giant planets and the estimate for the radio flux from extrasolar planets, using this scaling law, which we believe to be on more solid grounds both theoretically and observationally than previously suggested scaling laws.…”
Section: Introductionmentioning
confidence: 78%
“…Christensen (2010) summarized scaling laws for planetary magnetic fields that were proposed by different authors. Most of them assume a strong relation between field strength and rotation rate.…”
Section: Comparison To Other Field Predictionsmentioning
confidence: 99%
“…The columns in these models typically have widths that are large, in fact, close to the scale of the system, /L ∼ E 1/3 0.1, and have been argued to be an essential feature of Earth-like models (e.g. Christensen & Aubert 2006;Christensen 2010). The highly coherent axial flow structures are responsible for generating dipolar magnetic fields that are well aligned with the rotation axis.…”
Section: Rotating Convectionmentioning
confidence: 99%
“…In fact, typical E ∼ 10 −4 models cannot generate Earth-like magnetic fields without the presence of axially coherent columns (e.g. Sreenivasan & Jones 2006b;Christensen 2010;Miyagoshi et al 2010;Soderlund et al 2012Soderlund et al , 2013.…”
Section: Rotating Convectionmentioning
confidence: 99%
“…The Elsasser number Λ = B 2 /4πρczηΩ 0 , withρcz mean density in the convective envelope, η magnetic diffusivity, Ω 0 stellar rotation rate, B a characteristic magnetic field of the CZ, is useful to discuss this balance of terms in the Navier-Stokes (N.V.) equation. Depending on the amplitude of this number and on the balance assumed in the Navier-Stokes equation, various scaling of the magnetic field amplitude can be expected (Fauve and Pétrélis 2007;Christensen 2010): Fig. 12 Magnetic wreaths yielding in turn steady (case D3; top left), irregular (case D3a; top right) and quasi cyclic (cases D3b & S3; bottom left and right) magnetic butterfly diagrams Nelson et al (2013).…”
Section: Nonlinear Dynamo Effect Magnetic Activity and Cyclesmentioning
confidence: 99%